2021
DOI: 10.3390/brainsci11080974
|View full text |Cite
|
Sign up to set email alerts
|

Non-Suicidal Self-Injury: An Observational Study in a Sample of Adolescents and Young Adults

Abstract: Non-Suicidal Self-Injury (NSSI) is the self-inflicted destruction of body tissues without suicidal intent with a prevalence of 1.5% to 6.7% in the youth population. At present, it is not clear which emotional and behavioral components are specifically associated with it. Therefore, we studied NSSI in a clinical sample of youth using the Ottawa Self-injury Inventory and the Barratt Impulsiveness Scale 11. The Mann–Whitney test was used to compare the numerical responses provided to the tests. We found 54 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
2
4
0
1
Order By: Relevance
“…Adolescents experiencing gender incongruities are exposed to a greater emotional burden than cisgender ones, both because of the increased social pressures they face and the complex maturation of their emotional regulation skills [20]. Although previous research has indicated that individuals with an early onset of GD could experience higher distress than individuals with a late onset which are usually older and potentially better at coping with distress [17], our results agree with more recent literature data and could support the idea that adolescents who experience gender incongruence later in time probably have fewer opportunities to adapt to such emotional and social burden [21,36]. We know that adolescence itself is a critical period for the development of emotion regulation for several reasons, which include signi cant physical changes, brain development of regions involved in affect generation and regulation, including the limbic system and prefrontal cortex, alterations of high-level executive and social processes necessary for emotion regulation, including working memory, inhibitory control, abstract thinking, decision making and perspective taking, increasing need for independence, academic and work pressures and uctuating social relationships in increasingly complex social contexts [37].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Adolescents experiencing gender incongruities are exposed to a greater emotional burden than cisgender ones, both because of the increased social pressures they face and the complex maturation of their emotional regulation skills [20]. Although previous research has indicated that individuals with an early onset of GD could experience higher distress than individuals with a late onset which are usually older and potentially better at coping with distress [17], our results agree with more recent literature data and could support the idea that adolescents who experience gender incongruence later in time probably have fewer opportunities to adapt to such emotional and social burden [21,36]. We know that adolescence itself is a critical period for the development of emotion regulation for several reasons, which include signi cant physical changes, brain development of regions involved in affect generation and regulation, including the limbic system and prefrontal cortex, alterations of high-level executive and social processes necessary for emotion regulation, including working memory, inhibitory control, abstract thinking, decision making and perspective taking, increasing need for independence, academic and work pressures and uctuating social relationships in increasingly complex social contexts [37].…”
Section: Discussionsupporting
confidence: 90%
“…Aspects of body investment were expected to play a role in the prediction of NSSI, suicide and suicide attempts [45]. Moreover, it is widely thought that there is an emotion-regulatory function of self-harm, and several research results support the existence of an emotion dysregulation trait among people who engage in these behaviors, which could decrease the perception of negative affect in many different ways: both intrapersonal, arising from within a person, and/or interpersonal [21]. In adolescents with GD a bidirectional link between low protective attitudes towards one's body and greater di culty in regulating emotions seems to exist [20] considering that they must learn to control emotions in adaptive ways to promote social functioning and psychological well-being despite social rejection, stigma, discrimination, violence and victimization, low access to health care providers experienced in transgender health, and limited availability of a multidisciplinary team of experts [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender differences may also exist in help-seeking behaviours among individuals who engage in NSSI. Research suggests that females are more likely to seek professional help or disclose their self-harming behaviours to others, while males may be more reluctant to seek help due to stigma or perceptions of weakness [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kršenje zakonskih i moralnih odgovornosti prilikom zlouporabe javnih službi i neodgovornog trošenja financijskih sredstava, također ostavlja mogućnost pravnog sankcioniranja ovakvog ponašanja. 7…”
Section: Uvodunclassified